2013
DOI: 10.4161/bioe.26271
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights in genetic transformation of the probiotic yeastSaccharomyces boulardii

Abstract: Saccharomyces boulardii (S. boulardii) is a probiotic yeast related to Saccharomyces cerevisiae (S. cerevisiae) but with distinct genetic, taxonomic and metabolic properties. S. cerevisiae has been used extensively in biotechnological applications. Currently, many strains are available, and multiple genetic tools have been developed, which allow the expression of several exogenous proteins of interest with applications in the fields of medicine, biofuels, the food industry, and scientific research, among other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
3
25
0
2
Order By: Relevance
“…There have been several reports showing that S. boulardii is different from S. cerevisiae in terms of transformation procedures and limited genetic perturbation tools (2). In this study, we showed that existing plasmids and genetic tools currently used for S. cerevisiae could be readily applied to S. boulardii.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…There have been several reports showing that S. boulardii is different from S. cerevisiae in terms of transformation procedures and limited genetic perturbation tools (2). In this study, we showed that existing plasmids and genetic tools currently used for S. cerevisiae could be readily applied to S. boulardii.…”
Section: Discussionmentioning
confidence: 68%
“…Also, constitutive promoters, including pTDH3, pPGK1, and pTEF, have been employed for the overexpression of a target gene in conjunction with the use of the pRS series plasmids (27). While previous studies examined whether genetic tools of S. cerevisiae can be utilized for introducing genetic perturbations into S. boulardii (1,2), the examinations were limited because four common auxotrophic strains (ura3, his3, trp1, and leu2) of S. boulardii did not exist. As we obtained isogenic single or double mutants, which can be complemented by four auxotrophic markers, we were able to perform comprehensive evaluations of S. cerevisiae genetic tools in S. boulardii.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to molecular genetic techniques, S. boulardii considered originally as a yeast species by itself [7] has been proven in recent years to be a variant of S. cerevisiae [8]. In this chapter, a diploid yeast strain similar to those strains used in most research laboratories, amenable to genetic manipulation when using conventional yeast protocols is shown.…”
Section: Introductionmentioning
confidence: 99%